2020
DOI: 10.1002/ctm2.240
|View full text |Cite
|
Sign up to set email alerts
|

A selected small molecule prevents inflammatory osteolysis through restraining osteoclastogenesis by modulating PTEN activity

Abstract: A selected compound 17 small molecule suppressed osteoclastogenesis in vitro by inducing PTEN activity by restraining PTEN ubiquitination, thus inhibiting the RANKL-induced NF-κB pathway. The polarization and repolarization of M1 macrophages were also negatively modulated. In vivo experiments showed that compound 17 prevented LPS-induced inflammatory osteolysis by inhibiting OC activity. All in all, compound 17 might act as a potential novel drug to treat inflammatory osteolysis-related diseases in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…IL-1 can promote functional osteoclast differentiation synergistically with TNF-α ( 102 ). IL-1β also increases RANKL production in osteocytes and osteoblasts, promoting osteoclastogenesis ( 103 105 ). Moreover, IL-1β elevates M-CSF levels and decreases OPG levels ( 106 , 107 ).…”
Section: Mechanisms Of Bone Loss Related To Inflammasomesmentioning
confidence: 99%
“…IL-1 can promote functional osteoclast differentiation synergistically with TNF-α ( 102 ). IL-1β also increases RANKL production in osteocytes and osteoblasts, promoting osteoclastogenesis ( 103 105 ). Moreover, IL-1β elevates M-CSF levels and decreases OPG levels ( 106 , 107 ).…”
Section: Mechanisms Of Bone Loss Related To Inflammasomesmentioning
confidence: 99%
“… 57 Also, our TRAP staining verified that overactivated osteoclasts were blamed for inflammatory bone loss. 58 , 59 For treatment, intervening in the primary diseases and inhibiting inflammation are given priority. Thus, inhibiting immune cells, cytokine, osteoclastogenesis, and osteoclast activity is applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous to E6AP C terminus (HECT) domain ligases transfer ubiquitin to PTEN and induce its ubiquitination [ 102 ]. Y Chen and colleagues [ 103 ] prepared a small-molecule compound named compound 17 structurally based on heclin, a HECT ligase inhibitor, and found that this compound could inhibit the ubiquitination of PTEN in osteoclasts (derived from BMDMs) stimulated by RANKL and LPS, thereby inhibiting IκBα and NF-κB p65 phosphorylation and NF-κB nuclear translocation. Decreased release of NLRP3 and IL-1β restrained osteoclast activation and bone resorption capacity, which was protective against inflammatory osteolysis.…”
Section: Pyroptosis In Macrophagementioning
confidence: 99%